Pengaruh Pendapatan, Tanggungan Keluarga Dan Pendidikan Terhadap Pola Konsumsi Rumah Tangga Nelayan Kecamatan Danau Teluk Kota Jambi - Marhama, Putri; Baining , Mellya Embun; Andriani, Beid Fitrianova (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to determine and discuss the influence of income, family responsibilities and education on the consumption patterns of fishermen households in Danau Teluk subdistrict, Jambi city. This research uses primary data obtained directly from the first source either from individuals or individuals such as filling out questionnaires. The method used in this research is quantitative, namely multiple linear regression analysis processed using SPSS (Statistical Package For Social Science) 27 software. The results of the research that has been carried out show that income, family responsibilities have no effect on consumption patterns and education has an effect on consumption patterns. Based on data analysis in this research, these variables are valid and reliable. When testing classical assumptions with a normal distribution, multicollinearity and heteroscedasticity do not occur.